AI-Powered Interactive Learning Platforms for Modern Education - Praba. R; Sanjai. S (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
AI-powered interactive learning platforms represent a significant advancement in modern education, aiming to enhance the learning experience through personalized, engaging, and adaptive methodologies. These platforms leverage artificial intelligence to create dynamic educational environments that cater to the diverse needs of students, transforming traditional learning paradigms. The introduction of interactive 2D and 3D simulations allows learners to immerse themselves in subjects, making complex concepts more accessible and enjoyable. Gamification elements further motivate students by turning learning into an engaging game where they can earn rewards and achieve milestones, fostering a sense of accomplishment and commitment to their educational journey. Moreover, these platforms utilize real-time data analytics to tailor content according to individual learning styles and paces, ensuring that each student receives the support they need to master concepts effectively. This personalized approach not only enhances comprehension but also significantly improves information retention rates compared to conventional static content. The integration of bilingual resources promotes inclusivity, enabling students from various linguistic backgrounds to engage fully with the material. As educational institutions increasingly adopt these AI-driven solutions, they are not only addressing the challenges posed by overcrowded classrooms and varying student needs but are also preparing learners for a future where critical thinking, creativity, and problem-solving skills are paramount. In essence, AI-powered interactive learning platforms are redefining education by merging technology with innovative pedagogical strategies. They offer a holistic approach that goes beyond mere academic achievement, nurturing essential skills that will equip students for success in an ever-evolving world. As these platforms continue to evolve and expand their capabilities, they hold the potential to unlock every child’s learning potential, making education a more personalized and impactful experience for all.